Investigations of Caloric Regulation: Ingestion of an Acaloric Diet by Domesticated Rats - Maloney, Terrence D. (My University, 1972)
A series of experiments investigated the ingestion of an acaloric diet (composed mainly of vaseline and methyl cellulose) by rats. While animals on an ad-lib feeding schedule seemed able to regulate caloric intake adequately in the presence of this diet, animals on a 3 hr/day schedule did not. Although ingestion of this diet resulted in retarded weight gain, they did not learn to avoid ingesting it. However, the data indicate that they did form an aversion to a nutritionally adequate diet presented in conjunction with the acaloric diet. This failure to associate the acaloric diet with the consequences of its ingestion was explained in terms of "learned safety".
Keywords: Psychology; Psychology